METODE ALTMAN Z-SCORE: ANALISIS LAPORAN KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PERUSAHAAN MAKAN DAN MINUMAN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2018-2020 - Putri A, Meta; Octavia P, Dina; Maheswari, Made Rekma Adi (JEA17: Jurnal Ekonomi Akuntansi, 2021)
The impact of the Covid-19 pandemic on food &beverages industry companies is the government's advice not to leave the house and prohibit eating in all restaurants greatly affects the Food &Beverages industry. The decline in profit growth was felt by food and beverage companies. The purpose of the study was to analyze and interpret the bankruptcy method with Altman's Z-score. The population in this study was 26 food and beverage sub-sector manufacturing companies and samples were taken purposively to 13 food and beverage sub- sector manufacturing companies listed on the Indonesia stock exchange in 2018-2020. The results in this study provide an explanation that Altman's Z-score analysis should continue to be reviewed because it becomes a benchmark for the financial condition of the company in every period so that it can be a good signal for investors if the company strives to maintain financial stability.